Plasma Fibrinogen and Fibrin Degradation Product (FDP) in Preeclampsia (Medicine Today, 2019)
Introduction: Hypercoagulable state is seen in preeclampsia which acts as a risk factor for thromboembolism & DIC. Altered coagulation indices (serum Fibrinogen & FDP) have been reported in patients with preeclampsia and have been suggested as a sensitive marker for detection of bleeding complications. This study was carried out to compare the coagulation indices in preeclamptic women.Materials & Methods: This cross sectional study was conducted in the Department of Physiology, Dhaka Medical College (DMC), Dhaka from January to December 2014. Total 100 women aged 18 – 40 years were selected from the department of Obstetrics & Gynaecology of DMCH, Dhaka for this study. Among them 50 were preeclamptic and age matched 50 healthy nonpregnant women were considered as control group. Fibrinogen & Fibrin Degradation Product (FDP) were analyzed on automated coagulation analyzer.Result: In this study, serum Fibrinogen & FDP were significantly higher in preeclamptic than those of healthy women. Moreover, 100% & 64% preeclamptic patient had raised serum Fibrinogen & FDP respectively.Conclusion: From this study it can be concluded that serum Fibrinogen & FDP are directly related with preeclampsia.Medicine Today 2019 Vol.31(1): 36-38